Distribution and seasonal abundance of medically important flies in Sharkia Governorate, Egypt and their associated bacteria - Tharwat A. Selim; Nosiba S. Basher; Saber A. Riad; Ahmed M. Al-Shahat; Amr Hosny Hashem; Randa I. Eltaly; Enayat M. Elqady; Eman El-said; Fatma Z. Hamed; Naglaa Fathi Badr; Zeinab A. Shouaib; Mohammed E. Rashed; et al. (PLoS ONE, 2026)
Due to the medical importance of flies as mechanical vectors of numerous pathogens, accurate information on their distribution, abundance, and associated bacterial communities is essential. This study investigated the diversity, preliminary seasonal observations, and bacterial associations of medically important flies in Sharkia Governorate through field surveys conducted from 2022 to 2023. A total of twelve fly species belonging to five families Calliphoridae, Muscidae, Sarcophagidae, Piophilidae, and Phoridae were identified. Chrysomya megacephala exhibited marked seasonal variation, whereas Sarcophaga carnaria showed relatively stable activity. Chrysomya albiceps , Lucilia sericata , and Piophila casei were absent during winter despite their presence in summer. Musca domestica was the most abundant species across all seasons, with Muscidae representing the dominant family (p < 0.001), followed by Calliphoridae (p < 0.05), while other families were significantly less abundant. Biodiversity indices, including Shannon and Simpson metrics, indicated high species diversity throughout the year with a slight decline during winter. Evenness values reflected balanced species distribution, and the highest Fisher’s alpha and Margalef richness indices were recorded during summer, highlighting the influence of temperature on community structure. Bacterial analysis of M. domestica body surfaces revealed that 80% of isolates were pathogenic species, while 20% were classified as non-pathogenic. These findings emphasize the ecological and public health significance of flies and highlight their potential role in pathogen transmission within the study area.